SEVILLA, J., CANTERA, J. (eds.) (2001): 1001 refranes españoles con su correspondencia en alemán, árabe, francés, inglés, italiano, polaco, provenzal y ruso. - Romera, Irene (Eslavística Complutense, 2002)
Sin resumen